Concession-bargaining in Australian higher education: the case of the National Jobs Protection Framework. (2nd October 2021) - Vassiley, Alexis; Russell, Francis
ABSTRACT: Australian universities suffered significant financial losses due to the COVID-19 pandemic. The National Tertiary Education Union (NTEU) responded with a concession-bargaining strategy, offering university managements a National Jobs Protection Framework (NJPF), which traded pay reductions for job security measures. This article provides an account of the development, promotion, and eventual collapse of the NJPF. We analyse the arguments for and against the NJPF, drawing on contemporary material from its supporters and opponents, and insights from the literature on concession-bargaining. We conclude that concession-bargaining was an unsuccessful strategy for the union, and put forward an alternative industrial strategy.